2017
DOI: 10.5194/hess-21-5443-2017
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow characteristics from modeled runoff time series – importance of calibration criteria selection

Abstract: Abstract. Ecologically relevant streamflow characteristics (SFCs) of ungauged catchments are often estimated from simulated runoff of hydrologic models that were originally calibrated on gauged catchments. However, SFC estimates of the gauged donor catchments and subsequently the ungauged catchments can be substantially uncertain when models are calibrated using traditional approaches based on optimization of statistical performance metrics (e.g., NashSutcliffe model efficiency). An improved calibration strate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 48 publications
(91 reference statements)
1
68
1
Order By: Relevance
“…Not including the evaluation metrics in the optimization can lead to an inadequate depiction of those metrics (e.g. Pool et al, 2017). Including mean runoff and discharge timing as met- The models agree on the sign of the change Two models agree, one non−behavioural Two models disagree, one non−behavioural The models disagree on the sign of the change Two models non−behavioural All models non−behavioural…”
Section: Discharge Timingmentioning
confidence: 99%
“…Not including the evaluation metrics in the optimization can lead to an inadequate depiction of those metrics (e.g. Pool et al, 2017). Including mean runoff and discharge timing as met- The models agree on the sign of the change Two models agree, one non−behavioural Two models disagree, one non−behavioural The models disagree on the sign of the change Two models non−behavioural All models non−behavioural…”
Section: Discharge Timingmentioning
confidence: 99%
“…The IHAs were selected as optimization criteria to ensure that the hydrological model depicts the individual IHAs and, therefore, the species preferences as well as possible. This is necessary because hydrological models perform weakly in predicting IHAs if they are not included in the optimization process (Kiesel et al, ; Pool et al, ; Vigiak et al, ). The IHAs were selected based on Kakouei et al (), who investigated the most important and not cross‐correlated IHAs for the occurring species in the Treene and Kinzig.…”
Section: Methodsmentioning
confidence: 99%
“…Kakouei et al (2017) developed these linkages using the indicators of hydrological alteration (IHAs; Olden & Poff, 2003). Multiple studies showed that a successful representation of IHAs in hydrological models requires a targeted optimization process towards these IHAs (Pool, Vis, Knight, & Seibert, 2017). Kiesel et al (2017) developed a methodology for a tailored optimization of hydrological models for these IHAs.…”
mentioning
confidence: 99%
“…Further, because subbasin‐lumped models rely on semiphysical based empirical parameters, calibration and subsequent simulations are constrained to streamflow gauging locations with sufficient record length to obtain reliable prediction of ecological response to forcing factors such as land‐use conversion or climate change. Gridded distributed models, when compared with lumped empirical models, offer an advantage in predicting high‐flow events unless precipitation errors cause more error in streamflow than for the lumped empirical models (Cartwright, Caldwell, Nebiker, & Knight, ; Pool, Vis, Knight, & Seibert, ; Smith, Ellis, Wagner, & Peterson, ; Teutschbein, Grabs, Laudon, Karlsen, & Bishop, ).…”
Section: Introductionmentioning
confidence: 99%
“…Gridded distributed models, when compared with lumped empirical models, offer an advantage in predicting high-flow events unless precipitation errors cause more error in streamflow than for the lumped empirical models (Cartwright, Caldwell, Nebiker, & Knight, 2017;Pool, Vis, Knight, & Seibert, 2017;Smith, Ellis, Wagner, & Peterson, 2012;Teutschbein, Grabs, Laudon, Karlsen, & Bishop, 2018).…”
mentioning
confidence: 99%